2008
DOI: 10.1089/end.2007.0118
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Tubeless and Standard Percutaneous Nephrolithotomy

Abstract: Nephrostomy-free or tubeless PCNL reduces postoperative urinary leakage and local pain related to the drainage tube. It also minimizes hospital stay; the majority of patients were discharged from the hospital in fewer than 24 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
105
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 26 publications
6
105
3
5
Order By: Relevance
“…Since this report, several other investigators have confirmed that tubeless PCNL leads to shorter hospital stays and less postoperative pain (16,18,19) and decreased cost as compared to nephrostomy tube drainage (7,20). While most studies have utilized a ureteral stent in patients undergoing a tubeless PCNL, other investigators have recommended a "totally tubeless" approach (21,22).…”
Section: Discussionmentioning
confidence: 87%
“…Since this report, several other investigators have confirmed that tubeless PCNL leads to shorter hospital stays and less postoperative pain (16,18,19) and decreased cost as compared to nephrostomy tube drainage (7,20). While most studies have utilized a ureteral stent in patients undergoing a tubeless PCNL, other investigators have recommended a "totally tubeless" approach (21,22).…”
Section: Discussionmentioning
confidence: 87%
“…8 Literatürde tüpsüz PNL'nin hastanede kalış sü-resini kısalttığını ve analjezi gereksinimini azalttı-ğını vurgulayan birçok çalışma mevcuttur. [10][11][12][13] Standart bir operasyon sonrası takılan nefrostomi tüpünün, özellikle de geniş çaplı kateterlerin, hastanın ameliyat sonrası ağrı skorlarını artırdığı gös-terilmiştir. 3 Agrawal ve ark.nın prospektif, randomize çalışmalarında, tüpsüz hastalarda PNL sonrası ağrının istatistiksel olarak daha az ve hastanede kalış süresinin daha kısa olduğu vurgulanmış, ayrıca gruplar arasında kan kaybı yönünden de fark saptanmadığı bildirilmiştir.…”
Section: Discussionunclassified
“…3 Agrawal ve ark.nın prospektif, randomize çalışmalarında, tüpsüz hastalarda PNL sonrası ağrının istatistiksel olarak daha az ve hastanede kalış süresinin daha kısa olduğu vurgulanmış, ayrıca gruplar arasında kan kaybı yönünden de fark saptanmadığı bildirilmiştir. 13 Çalışmamızda da kan kaybı yönünden iki grup arasında fark bulunamamıştır. Tüpsüz grupta hastanede kalma süresinin daha kısa olduğu görülmüştür.…”
Section: Discussionunclassified
“…3,9,17,18 Minimizing drainage tubes inserted at the conclusion of these procedures can decrease pain profile associated with these procedures. Ultimately, there is potential to reduce patient hospital stay due to decreased analgesic requirements.…”
Section: Discussionmentioning
confidence: 99%